Pre-Service Teachers' Reflection of Teaching and Learning - Kamarudin, Lailatul Zuraidah (2003)
Reflective practice has been introduced in practicum for pre-service teachers for the purpose of evaluating teaching strengths and weaknesses. In many instances however, pre-service teachers did not reflect on their lessons and therefore, they were unable to seek alternative ways in improving their teaching. A few factors contributed to the problem. Among them was a lack of guidance from either the supervising lecturer or the cooperating teacher. Another reason was due to the lack of explicit instructions as to how reflections should be written. Using a qualitative case study, observations on pre-service teachers' classroom teaching were carried out, semi-structured interviews were conducted and weekly and daily reflections were analyzed. Findings revealed that the pre-service teachers reflected on seven categories of teaching knowledge. Six of the categories were to Shulman's (1987) categories of teaching knowledge and one was similar to Hanipah's (1999) 'Awareness of Self as Teachers'. Another category "Working Principles in Teaching" emerged from the data of this research. This research in particular focused on reflection-on action in English Language teaching. In future, more research should be conducted on reflection-on-action in the teaching of subjects such as Mathematics and Science. In addition, reflection-in-action should be carried out to seek how pre-service teachers resolve matters while teaching.